A note to the weathering process in the east Nepal Himalayas (Journal of Nepal Geological Society, 1981)
The variability of the climato-morphogeoetic processes of the Himalaya during the Quaternary was due-in addition to the global climatic variations of the Earth-to the orogenic changes of the volume and shape of these mountains. In this paper the main modellation features of weathering processes in the East Nepal Himalayas on the examples of the soil genesis and glacigenous stratigraphy accumulations are summarized. The rates of the original mountain vault destruction and transport of the disintegrated masses depend on the intensity of the weathering processes of rocks controlled by the climatic conditions, and are a function of the potential energy of the highest mountain massifs.